3 Nation Casing / Ku Nurul Sofia Afizal ... [et al.]. - Afizal, Ku Nurul Sofia; Amran, Nur Ain Syahira; Gyazali, Muhammad Azfar Hazziq; Abdul Kamil, Irfan Farhan (2025)
3 nation casing is inspired by a phone casing where the phone casing functions as a protector for the phone so that the phone remains physically intact and does not suffer damage when it falls or is hit by a strong impact. We chose the phone casing as our product because almost all people today have this phone because it can facilitate their users' affairs in terms of communication, business or entertainment. We have created a new evolution of the phone casing by adding three advantages in one phone casing. The first advantage is that we have added a powerbank on the back, providing a speaker and having shock proof which can act to save the phone from any damage. The 3 Nation Casing company is organized by four people, namely the administration manager, marketing manager, financial manager and operation manager. This is because we want to ensure that all movements in the 3 Nation Casing company run smoothly with the presence of each manager from the various sectors in the 3 Nation Casing company. With this, every process and progress in 3 Nation Casing will be more organized and structured from the various aspects in managing a company. More than that, we have chosen Shah Alam as the location to develop our company. Among the reasons why the Shah Alam location was chosen is because it is a strategic location to develop a company. This is because it is in the middle of the city and it is easy to attract the attention of people who live there. There is also a large human population there which can help increase sales if we establish a base there.